HBR working dads collection - Dowling, Daisy (Boston : Harvard Business Review Press, 2022)
Everything you need to have a successful career and be the dad you want to be. Finally, we've moved past the days when providing for your family meant taking a backseat role in your children's lives. Still, many working dads aren't finding the support and flexibility they need, and the time-management challenge of performing at work while being a present dad at home can feel impossible. The HBR Working Dads Collection can help you manage this tension. Drawing on the wisdom of world-class experts and parents alike, it provides practical advice on the topics most important to those who want to be great fathers and have impactful careers. The six books in this set-- Advice for Working Dads, Getting It All Done, Managing Your Career, Taking Care of Yourself, Communicate Better with Everyone, and Two-Career Families--will teach you how to transition into your new role as a working father, communicate effectively with your employer and your family, prioritize time to address your personal needs, and navigate being part of a two-career family. There's no one simple answer or foolproof tip to make working fatherhood easy, but the strategies in this collection can help set you on a path toward finding success, both in your career and as a dad. The HBR Working Parents Series with Daisy Dowling, Series Editor, supports readers as you anticipate challenges, learn how to advocate for yourself more effectively, juggle your impossible schedule, and find fulfillment at home and at work. Whether you're up with a newborn or planning the future with your teen, you'll find the practical tips, strategies, and research you need to make working parenthood work for you.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3
Keywords: Fathers -- Employment; Work-life balance; Quality of work life; Fathers -- Employment; Quality of work life; Work-life balance